Adverse effects of artificial illumination on bat drinking activity. (17th February 2017) - Russo, D.; Cistrone, L.; Libralato, N.; Korine, C.; Jones, G.; Ancillotto, L.
Abstract: Artificial illumination at night (ALAN) alters many aspects of animal behaviour. Commuting and foraging bats have been found to be affected by ALAN, but no study has yet addressed the impact of lighting on drinking activity, despite its critical importance for bats. We experimentally illuminated cattle troughs used by drinking bats at four forest sites in Italy, and compared drinking activity and foraging activity under lit and dark conditions. We predicted that (1) the number of bat species and drinking events will be lower under illumination and (2) forest bat species will be more affected than edge specialists. We recorded 2549 drinking events from 12 species or species groups, most of which decreased drinking activity under illumination. The effects of ALAN on drinking were stronger than on foraging. Forest species never drank when the light was on. Edge‐foraging species reduced drinking activity while also increasing foraging under lit conditions. We highlight a previously overlooked negative effect of ALAN on bats, whose implications may be locally catastrophic. Given the importance of water sites for both bat foraging and drinking, their illumination should be forbidden, appropriately mitigated or, if necessary, compensated for with the creation of alternative drinking sites. Abstract : We show that artificial illumination leads to a dramatic decrease in bat drinking activity. We found that lighting affects drinking behaviour more than foraging and that even species usually regarded as light‐tolerant exhibit adverse reactions to light when drinking. Illumination of drinking sites may therefore have considerably harmful consequences for bat conservation (Image courtesy of Jens Rydell).